Gender variability in the clinical phenotype of hypertrophic cardiomyopathy. (25th November 2020) - Wasserstrum, Y; Larranaga-Moreira, J.M; Lotan, D; Fernandez-Fernandez, X; Klempfner, R; Sabbag, A; Freimark, D; Monserrat, L; Arad, M; Barriales-Villa, R
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is a structural heart disease defined by an increase in left-ventricular (LV) wall thickness, that may be complicated with a clinical syndrome of heart failure, arrhythmia and death. Purpose: To characterize the clinically significant factors for female HCM patients and bring forward the awareness to gender-based differences in HCM. Methods: We reviewed the patient records of 1297 patients age ≥18 years, diagnosed with HCM, from two tertiary medical centers in Spain and Israel, and analyzed 748 male and female patients matched for age ≥60 years at admission, BMI, hypertension, diabetes and obstructive HCM. Results: Female patients were older at original diagnosis [median 54 years (38–66) vs. 50 years (35–60), p=0.007], and had higher rates of family history of both HCM (46% vs. 37%, p=0.01) and sudden cardiac death (23% vs. 15%, p=0.02). Female patients had lower rates of active smoking (11% vs. 25%, p<0.001) and coronary disease (3% vs. 8%, p=0.007). In echocardiographic studies, females had a smaller LV cavity both during diastole [median 42mm (39–46) vs. 46 (42–50), p<0.001] and during systole [median 24 (21–29) vs. 27 (23–31), p<0.001]. Female patients had higher rates of significant mitral insufficiency (37% vs. 19%, p<0.001), and despite no significant differences in the rates of obstructive HCM, diastolic dysfunction, left-atrial enlargement, atrial fibrillation, ventricular tachyarrhythmia or pulmonary disease, they also had more significant pulmonary hypertension (≥45mmHg, 29% vs. 14%, p<0.001). Women had a lower functional capacity (p<0.001 for differences in NYHA, see fig.), and lower exercise capacity [median 7.0 METs (5–10) vs. 10.0 (7–12), p<0.001) and more abnormal blood pressure response to exercise (35% vs. 26%, p=0.03). Electrocardiographic features were similar across genders, except for a non-clinically significant shorter QRS duration in females. No significant differences were seen in 5-year mortality follow-up, which was ∼3% in the entire cohort. Conclusions: Female patients suffering from HCM have a clinical phenotype defined by slightly later presentation (and shorter time until admission to a tertiary-center cardiomyopathy clinic), smaller LV cavity size, higher severity of mitral insufficiency and pulmonary hypertension and worse functional and exercise capacities. Genders did not differ in 5-year mortality, which was relatively low. Funding Acknowledgement: Type of funding source: None